The Impact of Regulation Policy In Indonesia Against Women's Family Head - Kuswanti, Ana; Saleh, Amiruddin; Hubeis, Aida Vitayala S; Puspitawati, Herien; Muqsith, Munadhil Abdul (Jurnal Cita Hukum, 2020)
Abstract. The female head of the family has a dual role, that is, a housewife and breadwinner to meet family needs. The study aims to analyze the effect of female head of household characteristics and group characteristics on participatory communication of groups and economic independence of women household heads. Respondents were Pekka groups in twelve villages in Batang City, Central Java, as many as 229 heads of households aged 22-74 years. The characteristics measured include 5 dimensions namely: age, education, marital status, number of dependents, and income. Data were analyzed descriptively and multiple linear regression testing was carried out. The results showed that there was a direct positive effect on the characteristics of female household heads in participatory communication and the economic independence of female household heads. and there is a direct negative effect on group characteristics on participatory communication and the economic independence of the female household headKeywords: regulation effect, female head of a family, Pekka group, economic independence Abstrak.Kepala keluarga perempuan memiliki peran ganda, yaitu, seorang ibu rumah tangga dan pencari nafkah untuk memenuhi kebutuhan keluarga. Penelitian ini bertujuan untuk menganalisis pengaruh karakteristik kepala rumah tangga perempuan dan karakteristik kelompok terhadap komunikasi partisipatif kelompok dan kemandirian ekonomi kepala rumah tangga perempuan. Responden adalah kelompok Pekka di dua belas desa di Kota Batang, Jawa Tengah, sebanyak 229 kepala keluarga berusia 22-74 tahun. Karakteristik yang diukur meliputi 5 dimensi yaitu: usia, pendidikan, status perkawinan, jumlah tanggungan, dan pendapatan. Data dianalisis secara deskriptif dan dilakukan uji regresi linier berganda. Hasil penelitian menunjukkan bahwa ada pengaruh positif langsung pada karakteristik kepala rumah tangga perempuan dalam komunikasi partisipatif dan kemandirian ekonomi kepala rumah tangga perempuan. Selain itu, ada efek negatif langsung pada karakteristik kelompok pada komunikasi partisipatif dan kemandirian ekonomi kepala rumah tangga perempuanKata kunci: efek regulasi, kepala keluarga wanita, kelompok Pekka, kemandirian ekonomi Аннотация.Женщина как глава семьи играет двойную роль, то есть роль домохозяйки и кормильца семьи. Цель исследования - проанализировать влияние характеристики женщин как главы семьи и групповой характеристики на групповое совместное общение и экономическую независимость женщин как главы семьи. Респондентой была группа Pekka (Полномочия семей с женщинами как главами семьи) в двенадцати деревнях в городе Батанг, в Центральной Яве, 229 глав семьи в возрасте 22-74 лет. Измеренные характеристики включают 5 параметров, а именно: возраст, образование, семейное положение, количество иждивенцев и доход. Данные были проанализированы описательно, и было проведено множественное линейное регрессионное тестирование. Результаты показали, что непосредственное положительное влияние оказали характеристики женщин как глава семьи в совместном общении и экономической независимости. Кроме того, существует прямое негативное влияние на групповые характеристики на совместное общение и экономическую независимость женщин как глав семьи.Ключевые слова: Эффект регулирования, Женщина как глава семьи, Группа Pekka, Экономическая независимость.